2002
DOI: 10.1002/1522-2683(200209)23:17<2913::aid-elps2913>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of selenium and antimony compounds by capillary electrophoresis with indirect fluorescence detection

Abstract: Capillary electrophoresis (CE) with indirect fluorescence detection was used to analyze selenium (selenite, selenate, selenomethionine, and selenocystine) and antimony (antimonite and antimonate) compounds. The separation was achieved by CE in 6 min with a 1.2 mM fluorescein solution at pH 9.5. Fluorescein also functioned as a background fluorophore for the indirect detection of these nonfluorescent species. Linearity of more than two orders of magnitude was generally obtained. Precision of migration times and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 19 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…The CE-LIF system was assembled in-house and has been described previously [25,26]. A 0-30 kV power supply (GAMMA high voltage research Inc., Ormond Beach, FL, USA) provided the separation voltage.…”
Section: Ce-lif Systemmentioning
confidence: 99%
“…The CE-LIF system was assembled in-house and has been described previously [25,26]. A 0-30 kV power supply (GAMMA high voltage research Inc., Ormond Beach, FL, USA) provided the separation voltage.…”
Section: Ce-lif Systemmentioning
confidence: 99%
“…A comprehensive review on LOC technologies can be found in [14,15]. A large number of microfluidic devices rely on electrokinetic phenomena to realise various unit operations such as mixing of liquids [16], electrokinetic (electro-osmotic) pumping [17,18], separation of ions [19,20] and the manipulation of particles/cells [21][22][23]. All electrokinetic phenomena are related to the presence of an electrical double layer (EDL).…”
Section: Introductionmentioning
confidence: 99%
“…Although indirect LIF (ILIF) cannot achieve the merit with respect to both high sensitivity and universal detection by the combination of LIF detection and retro‐reflected beam interference detection 31, yet simple operations without derivatization were obtained and it would extend the application range of LIF detection. The utilization of ILIF detection for the analysis of valproic acid 32, explosives 33, 34, alcohols 35, arsenic species 36, selenium and antimony compounds 37, thiols 38, inorganic anions 39, diuretics 40, VX and its methylphosphonic acid degradation products 41, coumarin compounds 42 and adenine and guanine 43 has been reported in recent years. In addition, investigations on protein‐drug interaction 44, estimation of p K a values 45 and the determination of EOF of PMMA microfluidic chip 46 by means of ILIF were also conducted.…”
Section: Introductionmentioning
confidence: 99%